Intraspecific Functional Trait Response to Advanced Snowmelt Suggests Increase of Growth Potential but Decrease of Seed Production in Snowbed Plant Species - Tonin, Rita; Gerdol, Renato; Tomaselli, Marcello; Petraglia, Alessandro; Carbognani, Michele; Wellstein, Camilla (Frontiers in Plant Science, 2019)
In ecological theory, it is currently unclear if intraspecific trait responses to environmental variation are shared across plant species. We use one of the strongest environmental variations in alpine ecosystems, i.e. advanced snowmelt due to climate warming, to answer this question for alpine snowbed plants. Snowbeds are extreme habitats where long-lasting snow cover represents the key environmental factor affecting plant life. Intraspecific variation in plant functional traits is a key to understand performance and vulnerability of species in a rapidly changing environment. We sampled snowbed species after an above-average warm winter to assess their phenotypic adjustment to advanced snowmelt, based on differences in the natural snowmelt dynamics with magnitudes reflecting predicted future warming. We measured nine functional traits related to plant growth and reproduction in seven vascular species comparing snowbeds of early and late snowmelt across four snowbed sites in the southern Alps, Italy; the early snowbeds providing a proxy for the advanced snowmelt caused by climatic warming. Seed production was reduced under advanced snowmelt in all seed-forming snowbed species. Higher specific leaf area (SLA) and lower leaf dry matter content (LDMC) were indicative of improved growth potential in most seed-forming species under advanced snowmelt. We conclude, first, that in the short term advanced snowmelt can improve snowbed species’ growth potential. However, in the long term results from other studies hint at increasing competition in case of ongoing improvement of conditions for plant growth under continued future climate warming representing a risk for snowbed species. Second, a lower seed production can negatively affect the seed rain. A reduction of propagule pressure can be crucial in a context of loss of the present snowbed sites and the formation of new ones at higher altitudes along with climate warming. Finally, our findings encourage using plant functional traits at the intraspecific level across species as a tool to understand the future ecological challenges of plants in changing environments.